Mortality trend due to traffic accident in young in the south of Brazil - Willian Augusto de Melo; Rosana Rosseto de Oliveira; Adriano Brischiliari; Sandra Marisa Pelloso; Maria Dalva de Barros Carvalho (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2018)
Abstract Background Traffic accidents are a major global public health problem with an impact on morbidity and mortality. Objective The aim of this study was to analyze the mortality trend from road accidents among young adults. Method An ecological time-series study was performed of the deaths of young (15-24 years old) in traffic accidents in the state of Parana, Brazil from 1996 to 2013. Mortality data was obtained from the Mortality Information System. Mortality rates were calculated and the trend analysis was performed through polynomial regression models. A trend was considered significant when the estimated model obtained a p-value <0.05. Accidents involving tricycles were excluded from the analysis (58 cases). Results Of the 12,063 deaths from road accidents, 82.0% were male. There was a significant and growing trend of accident mortality rates involving motorcyclists and car and pick-up truck occupants, and a decreasing trend of fatal accidents involving pedestrians. The average mortality rate for accidents involving motorcyclists was 10 deaths per 100,000 residents, an increase of 1.13 per year. Accidents involving car occupants increased annually by 0.43 and accidents involving pick-up truck occupants by 0.01. Conclusion There was a significant increasing trend for fatalities of both genders, especially motorcyclists and car occupants. The pedestrian mortality trend has shown a decreasing due to their lower exposure.